Response to withdrawal of vitamin and trace mineral premixes from finisher diet in broiler chickens under the hot and humid tropical conditions - Mochamat, Norasyikin; Idrus, Zulkifli; Farjam, Abdoreza Soleimani; Hossain, Mohammad Abul (Taylor & Francis Group, 2017)
This study was conducted to assess the effects of omitting vitamin (VIT) and trace mineral (TRM) premixes from the finisher diet on growth performance, antibody production against Newcastle disease (ND) vaccination, leg bone strength and incidence of foot pad dermatitis (FPD) in male and female broiler chickens. Birds were raised on floor pens in a naturally ventilated house using wood shavings as litter. Commencing from day 21, equal number of male and female birds were subjected to one of four VIT and TRM premixes withdrawal treatments as follows: (i) withdrawal from 21 to 42 days, (ii) withdrawal from 28 to 42 days, (iii) withdrawal from 35 to 42 days, and (iv) no withdrawal (control). In comparison to the control group, feed intake, body weights, feed conversion ratios and antibody responses to Newcastle disease vaccination were not affected by any of the supplement withdrawal treatment. Male birds had lower antibody production and higher bone-breaking strength as compared to their female counterparts. Irrespective of gender, withdrawal of VIT and TRM premixes from 21 to 42, and 28 to 42 days adversely affected bone-breaking strength. In conclusion, VIT and TRM premixes can be removed from the diet of male and female broiler chickens from 21 to 42 days without any adverse effects on growth performance, mortality, antibody response and incidence of foot pad dermatitis. However, bone-breaking strength was adversely affected by the withdrawal of VIT and TRM premixes for more than seven days.